THE PRACTICE OF DEVELOPING THE DIGITAL ECONOMY IN COUNTRIES AROUND THE WORLD - Zuhra Maratdaevna Otaquzieva; Berdiboev Oltinboy Abdiboqi ogli (International Engineering Journal For Research & Development, 2021)
This article examines and analyzes the practice of digital economy development in the countries of the world, developed and developing countries, its indicators, directions of digital technology development